β-Catenin Knockdown in Liver Tumor Cells by a Cell Permeable Gamma Guanidine-based Peptide Nucleic Acid - Delgado, Evan; Bahal, Raman; Yang, Jing; M. Lee, Jung; H Ly, Danith; P. S. Monga, Satdarshan (Current Cancer Drug Targets, 2013)
Hepatocellular cancer (HCC) is the third cause of death by cancer worldwide. In the current study we target &bgr- catenin, an oncogene mutated and constitutively active in 20-30% of HCCs, via a novel, cell permeable gamma guanidine-based peptide nucleic acid (γGPNA) antisense oligonucleotide designed against either the transcription or the translation start site of the human &bgr-catenin gene. Using TOPflash, a luciferase reporter assay, we show that γGPNA targeting the transcription start site showed more robust activity against &bgr-catenin activity in liver tumor cells that harbor &bgr-catenin gene mutations (HepG2 & Snu-449). We identified concomitant suppression of &bgr-catenin expression and of various Wnt targets including glutamine synthetase (GS) and cyclin-D1. Concurrently, γGPNA treatment reduced proliferation, survival and viability of HCC cells. Intriguingly, an angiogenesis quantitative Real-Time-PCR array identified decreased expression of several pro-angiogenic secreted factors such as EphrinA1, FGF-2, and VEGF-A upon &bgr-catenin inhibition in liver tumor cells. Conversely, transfection of stabilized-&bgr-catenin mutants enhanced the expression of angiogenic factors like VEGF-A. Conditioned media from HepG2 cells treated with &bgr-catenin but not the mismatch γGPNA significantly diminished spheroid and tubule formation by SK-Hep1 cells, an HCC-associated endothelial cell line. Thus, we report a novel class of cell permeable and efficacious γGPNAs that effectively targets &bgr-catenin, a known oncogene in the liver. Our study also identifies a novel role of &bgr-catenin in liver tumor angiogenesis through paracrine mechanisms in addition to its roles in proliferation, survival, metabolism and cancer stem cell biology, thus further strengthening its effectiveness as a therapeutic target in HCC.
Keywords: proliferation and antisense